Pengaruh Pemberian Pupuk Organik Ampas Sagu (Metroxylon sagu Rott) Terhadap Pertumbuhan dan Produksi Tanaman Seledri (Apium graveolens L.) - Suryani Suryani; Akhmad Gazali; Antar Sofyan (Agroekotek View, 2020)
Celery (Apium graveolens L.) is a vegetable that is useful as a spice. Besides this plant is also used as ingredients for medicines and cosmetics. One of them is in the form of organic plant waste. So that in this study I took sago waste waste that is not utilized by the people in Tanah Bumbu, this study aims to determine the effect of organic sago waste waste and find out the best dose for the growth and production of celery plants. This research has been carried out in the Experimental Garden of the Wahana Loktabat Utara Institute of Banjarbaru, South Kalimantan from May to August 2019. This study used a 1-factor Randomized Complete Design (RAL) with five treatments four replications. The treatment is in the form of k0: without organic fertilizer sago pulp, k1: 10 tons ha-1 organic sago pulp 50 g / plant, k2: 20 tons ha-1 organic sago pulp 100 g / plant, k3: 30 tons ha-1 organic pulp sago 150 g / plant, k4: 40 tons ha-1 organic sago pulp 200 g / plant. Based on the results of the organic fertilizer dosage did not have a significant effect on plant height parameters, number of tillers and wet weight, but had a significant effect on leaf width in the 2nd, 4th and 5th weeks. Whereas the best dose of organic fertilizer for sago pulp only occurs in the leaf width parameter of the 2nd week with k2 treatment, the 4th week with k3 treatment and the 5th week with k4 treatment.